CDT1 Is a Novel Prognostic and Predictive Biomarkers for Hepatocellular Carcinoma - Cai, Chenhui; Zhang, Ying; Hu, Xu; Hu, Wenhui; Yang, Sizhen; Qiu, Hao; Chu, Tongwei (Frontiers in Oncology, 2021)
Objective Hepatocellular carcinoma (HCC) is one of the most common malignant tumors endangering human health and life in the 21st century. Chromatin licensing and DNA replication factor 1 (CDT1) is an important regulator of DNA replication licensing, which is essential for initiation of DNA replication. CDT1 overexpression in several human cancers reportedly leads to abnormal cell replication, activates DNA damage checkpoints, and predisposes malignant transformation. However, the abnormal expression of CDT1 in HCC and its diagnostic and prognostic value remains to be elucidated. Methods TCGA, ONCOMINE, UALCAN, HCCDB, HPA, Kaplan-Meier plotter, STRING, GEPIA, GeneMANIA, and TIMER were conducted for bioinformatics analysis. CDT1 protein expression was evaluated by immunohistochemistry in HCC tissues through a tissue microarray. qRT-PCR, western blot and a cohort of functional experiments were performed for in vitro validation. Results In this study, we discovered remarkably upregulated transcription of CDT1 in HCC samples relative to normal liver samples through bioinformatic analysis, which was further verified in clinical tissue microarray samples and in vitro experiments. Moreover, the transcriptional level of CDT1 in HCC samples was positively associated with clinical parameters such as clinical tumor stage. Survival, logistic regression, and Cox regression analyses revealed the significant clinical prognostic value of CDT1 expression in HCC. The receiver operating characteristic curve and nomogram analysis results demonstrated the strong predictive ability of CDT1 in HCC. Kyoto Encyclopedia of Genes and Genomes and gene set enrichment analyses indicated that CDT1 was mainly associated with the cell cycle, DNA repair, and DNA replication. We further demonstrated the significant correlation between CDT1 and minichromosome maintenance (MCM) family genes, revealing abnormal expression and prognostic significance of MCMs in HCC. Immune infiltration analysis indicated that CDT1 was significantly associated with immune cell subsets and affected the survival of HCC patients. Finally, knockdown of CDT1 decreased, whereas overexpression of CDT1 promoted the proliferation, migration, invasion of HCC cells in vitro. Conclusions Our study findings demonstrate the potential diagnostic and prognostic significance of CDT1 expression in HCC, and elucidate the potential molecular mechanism underlying its role in promoting the occurrence and development of liver cancer. These results may provide new opportunities and research paths for targeted therapies in HCC.